2016
DOI: 10.1002/ajoc.201600430
|View full text |Cite
|
Sign up to set email alerts
|

A General and Efficient Synthesis of 2‐Pyridones, 2‐Quinolinones, and 1‐Isoquinolinones from Azine N‐Oxides

Abstract: 2‐Pyridones, 2‐quinolinones, and 1‐isoquinolinones are critical building blocks in medicinal chemistry. These N‐heterocycles, however, remain a challenge to synthesize by current methods. A mild, general, and efficient approach for the synthesis of these hydroxyl N‐heteroarenes was developed by employing bromotripyrrolidinophosphonium hexafluorophosphate (PyBroP) as an activating agent and sodium acetate/water as the base/nucleophile combination. The reaction mechanism, especially the dual function of sodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Selective aldehyde deformylation of 3a mediated by aqueous NaOH has resulted in the formation of N-(tert-butyl)quinolin-2-amine 6 with 60% yield (Scheme 5). [21] Apart from the traditional FT-IR, 1 H & 13 C NMR and mass spectral analysis, the formation of N-(quinolin-2-yl)formamide was also unambiguously verified by X-ray crystallography of compounds 3 f and 3 o (Figure 2). The crystallographic data and structure refinement parameters are given in the supporting information (Table S1).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Selective aldehyde deformylation of 3a mediated by aqueous NaOH has resulted in the formation of N-(tert-butyl)quinolin-2-amine 6 with 60% yield (Scheme 5). [21] Apart from the traditional FT-IR, 1 H & 13 C NMR and mass spectral analysis, the formation of N-(quinolin-2-yl)formamide was also unambiguously verified by X-ray crystallography of compounds 3 f and 3 o (Figure 2). The crystallographic data and structure refinement parameters are given in the supporting information (Table S1).…”
Section: Resultsmentioning
confidence: 88%
“…From the variable-temperature 13 C NMR experiments in DMSO-d 6 , it was observed that broadening for a subset of 13 C NMR peaks at higher temperatures, which is due to the dynamic exchange between the two rotamers (Figure 4a-g). The complete resolved 13 C NMR signals were achieved at 60 °C, where the conformation interconversion is fast on the NMR time scale. The reversibility of these changes were verified when the experimental temperature was returned to 25 °C (Figure 4a-i).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group developed a mild and efficient alternative, employing sodium acetate, water, and PyBroP as the activating agent (Scheme 34). [56] Notably, this method has a wide substrate scope, including both electron‐rich and electron‐poor quinolines, pyridines, and isoquinolines.…”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%
“…Aromatic N ‐oxides (ArN→O) have been widely used as structural motifs in various fields due to their increased reactivity towards either electrophilic or nucleophilic agents compared to regular nitrogen heterocycles (Mfuh and Larionov, 2015). The appropriate N ‐oxides of pyridines, pyrazines, pyrimidines and quinolines are precursors for a huge variety of C2‐functionalized bioactive compounds used in medicine today (Wang et al ., 2016). No less important are N ‐oxides themselves as N → O moiety is present in various pharmaceuticals, chemical catalysts, agriculture agents and pyrotechnic compounds, and they are promising units in future studies as well (Dyer et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%